menu
QAmmunity.org
Login
Register
My account
Edit my Profile
Private messages
My favorites
Register
Ask a Question
Questions
Unanswered
Tags
Categories
Ask a Question
-3(1 + 6x) = 14 - x How do you solve this?
asked
Jul 12, 2020
12.0k
views
3
votes
-3(1 + 6x) = 14 - x
How do you solve this?
Mathematics
middle-school
Scottysmalls
asked
by
Scottysmalls
4.3k
points
answer
comment
share this
share
0 Comments
Please
log in
or
register
to add a comment.
Please
log in
or
register
to answer this question.
1
Answer
4
votes
-3(1+6x) = 14 - x
-3 -18x = 14 -x
-18x +x = 14 + 3
-17x = 17
x = -17/17
x = -1
Therefore x is equal to -1.
Irio
answered
Jul 18, 2020
by
Irio
5.9k
points
ask related question
comment
share this
0 Comments
Please
log in
or
register
to add a comment.
Ask a Question
Welcome to QAmmunity.org, where you can ask questions and receive answers from other members of our community.
5.7m
questions
7.4m
answers
Other Questions
Evaluate a + b when a = –16.2 and b = –11.4 A. –27.6 B. –4.8 C. 4.8 D. 27.6
What is the value of x? (-4) - x = 5
Can someone help me with 5??? ASAP?
185g in the ratio 2:3
(3x1,000,000)+(3x100,000)+(2x100) what is this number written in standard form?
Twitter
WhatsApp
Facebook
Reddit
LinkedIn
Email
Link Copied!
Copy
Search QAmmunity.org